Patient decision aids for patients with differentiated thyroid carcinoma: development process and alpha and beta testing - Koot, Anna; Hermens, Rosella; Ottevanger, Petronella; Netea-Maier, Romana; Stalmeier, Peep; , the COMBO study group; Snel, Marieke; van der Kleij-Corssmit, Noortje; Bonenkamp, Johannes; Dreijerink, Koen; van Dam, Evelien; Nieuwenhuijzen, Grard; et al. (Frontiers in Endocrinology, 2023)
Background: Patient decision aids (PtDAs) are structured clinical tools that facilitate shared decision making. Two important treatment decisions for patients with differentiated thyroid cancer (DTC), which could benefit from PtDAs, are: 1) the extent of surgery decision in patients with low-risk DTC and 2) the decision to start or delay starting the treatment with Tyrosine Kinase Inhibitors (TKIs) in patients with advanced tumors. Material and methods: PtDAs for these two decisions were developed using the International Patient Decision Aids Standards (IPDAS) quality criteria in an iterative process of prototype development, via alpha and beta testing by patients and physicians. Information content of the PtDAs was based on the available literature, current guidelines and patients’ needs, preferences and values. Results: The web-based PtDAs underwent two rounds of alpha testing, revisions and a beta testing. The PtDAs have the same structure, consisting of six steps, being a general introduction, information about the treatment options, comparing the treatment options, knowledge questions, a values clarification exercise, and saving the information. The alpha testing (n=8 patients, n=10 physicians) showed that the PtDAs were highly acceptable and usable for decision making. Results of the beta testing in 20 patients showed that two patients did not use the PtDA, the other 18 patients found that the PtDAs were readable (n=17) and helpful (n=14) for decision making. All patients recommend using the PtDAs. Conclusions: Evidence-based PtDAs were created for patients with DTC for two different treatment decisions. Our final version was judged to be clear, balanced and helpful in decision making.